Teaching Campus as A Mean for Improving Primary School Creativity: (Kampus Mengajar Sebagai Wadah Peningkatan Kreativitas Sekolah Dasar) - Hutapea, Elisabet Ronauli; Tuti Atika (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
The Campus Teaching Program (KM) is part of the MBKM initiative that opens opportunities for students to spend one semester outside the campus. The goal of this program is to train students' skills in addressing issues by collaborating with teachers, innovating in teaching, developing creative, innovative, and enjoyable learning strategies. The Campus Teaching Program is organized with the aim of training students in personal development beyond the scope of regular lectures. This initiative aims to provide students with the opportunity to empower educators in Elementary Schools (SD) and Junior High Schools (SMP) through face-to-face learning activities. Students play a crucial role as change agents with the hope of contributing to the improvement of education quality, especially in literacy and numeracy at the elementary and junior high school levels. Participation in the campus teaching program does not automatically transform students into classroom teachers. Instead, the goal is to collaborate with teachers in efforts to enhance literacy, numeracy, and the application of technology in the focused schools. The program provides students with the opportunity to apply their knowledge and skills in supporting the development of students in the educational environment. The approach applied is the service learning method, which integrates the material and theory acquired by students and applies it in the form of real contributions through community service.